Cost of Illness Type 2 Diabetes Mellitus Outpatient BPJS on Malang City Health Center - Ika Ratna Hidayati; Aniza Oktaviana; Liza Pristianty (Universitas Airlangga, 2022)
Background: Type 2 diabetes mellitus is a progressive illness that impacts the costs borne by patients. The Cost of Illness method can be used further to analyze the medical expenses for type 2 diabetes mellitus. Objective: Determine the annual total cost of type 2 diabetes mellitus outpatients in Indonesia Health Insurance (BPJS) participants and treated with metformin-glibenclamide. Methods: This study applied the non-probability sampling technique and the purposive sampling method to the cross-sectional approach. The research was conducted in the Mulyorejo Health Care of Malang City, using 58 patients as samples. The research instrument involves a systematic interview that has been tested for its validity. The data were analyzed using Microsoft Excel. Results: The direct medical cost per patient is IDR 173,560.00 – IDR 1,266,240.00. Non-medical direct cost is IDR 0.00 – IDR 240,000,00. The indirect cost is IDR 0.00 – IDR 1,920.000,00. Conclusion: The estimated annual total medical expenses of diabetes mellitus type 2 Indonesia Health Insurance (BPJS) outpatients employing metformin-glibenclamide therapy at Mulyorejo Health Center in Malang is IDR 173,560.00 – IDR 3,426,240.00.